POLITIK DALAM KARYA SENI LUKIS KONTEMPORER - SRI WAHYUNI, Drs. Irwan, M.Sn, Yasrul Sami, S.Sn., M.Sn (Serupa The Journal of Art Education, 2014)
Politic in Painting Art, final work. Arts Education, Faculty of Language and Arts, State University of Padang. Politic that human improve is an activity related to the problem in compete and keep an authority in a country through organizations and interpretation of the convention inorder to achieve the national objectives. The purpose of this final work is to visualize the politic promisses in the form of contemporary paint art. The titles of the politik in painting art work are “Sebuah Janji”, “Dua Sisi Yang Berbeda Satu Tujuan”, “Umbar Janji”, “Janji Di Ujung Lidah”, “Berterbangan”, “Black Campaign”, “Partisipasi Janji Politik”, “Akar Janji Politik”, “Wajah Berkabut”, “Putih Meleleh dan Hitam Merajalela”.Kata kunci: Janji-janji Politik, Lukisan Kontemporer